A manager's guide to the new world of work the most effective strategies for managing people, teams, and organizations (The digital future of management series from MIT Sloan Management Review, 2020)
"This volume examines the micro and macro components of today's companies, from people up to organizations, and the roles and strategies that enable smooth transitions and successful collaboration"--